The role of tooth preparation modification on retention and resistance in short abutment - Tiopan, Steven; Ariyani; Z. Tamin, Haslinda (Indonesian Journal of Prosthodontic, 2024)
Background: The parameters for the long-term success of fixed dentures are retention and resistance. Fixed denture treatment for short abutments requires modification of tooth preparation to increase retention and resistance. The proximal area of the preparation can be modified to increase retention by adding grooves, boxes, and frustums. To increase resistance, proximal modifications in the form of adding grooves and boxes, and cervical angle of convergence modification can be used. Objectives: To analyze retention and resistance based on convergence angle and tooth preparation modification on short abutment. In abutment with ideal convergence angle, addition of grooves and boxes will causes the cement-restoration interface to increase. The frustrum-shaped preparation will convert the retention value from the shear strength of the cement material into the compressive strength of the cement material. In abutment with compromised convergence angle, proksimal modification in the form of grooves and boxes, as well as reducing the convergence angles in the cervical region will result in paralleling of axial walls and increase the resistance. Conclusion: In cases of a short abutment with an ideal convergence angle, the highest retention is obtained by modifying the proximal area with a frustum shape. Meanwhile, if the convergence angles are compromised, reducing the convergence angle in the cervical region would be the most effective method to improve the resistance.